Recent advances towards azobenzene-based light-driven real-time information-transmitting materials - García-Amorós, Jaume; Velasco, Dolores (Beilstein Journal of Organic Chemistry, 2012)
Photochromic switches that are able to transmit information in a quick fashion have attracted a growing interest within materials science during the last few decades. Although very fast photochromic switching materials working within hundreds of nanoseconds based on other chromophores, such as spiropyranes, have been successfully achieved, reaching such fast relaxation times for azobenzene-based photochromic molecular switches is still a challenge. This review focuses on the most recent achievements on azobenzene-based light-driven real-time information-transmitting systems. Besides, the main relationships between the structural features of the azo-chromophore and the thermal cis-to-trans isomerisation, the kinetics and mechanism are also discussed as a key point for reaching azoderivatives endowed with fast thermal back-isomerisation kinetics.
Keywords: kinetics; light-controlled materials; molecular switches; photochromic switches; push–pull azophenols; thermal isomerisation